PRAKTIK EDUKASI SEBAGAI UPAYA PEMERTAHANAN EKSISTENSI FUNGSIONALISME BUDAYA PADA SANGGAR PASINAON PAMBIWARA KERATON SURAKARTA - Noviana, Renzi; Parahita, Bagas Narendra; Liestyasari, Siany Indria (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2024)
Culture is a valuable asset that needs to be preserved. Through this, there is a need for educational practices for the community as an effort to preserve culture. One of them can be done through Sanggar Pasinaon Pambiwara Keraton Surakarta. In its educational practice, this studio provides material about Javanese culture from the perspective of the Surakarta Palace for a period of six months. The purpose of this study is to examine the educational practices carried out by Sanggar Pasinaon Pambiwara Keraton Surakarta as an effort to maintain the existence of Javanese culture using Malinowski's functionalisme theory analysis framework. This research was conducted in Sanggar Pasinaon Pambiwara Keraton Surakarta, precisely in Marcukundha Ward. The research method used is qualitative research with the type of intrinsic case study research method. The results showed that there are several roles of the studio, namely the role of class learning and the role in palace activities. The elements that support the running of the studio include the founder, pangayom, pamong, dwija, and the Yayasan Kebudayaan Keraton Surakarta. The educational practices carried out by the studio have fulfilled three needs, including activities on the beach after the Nyekar dhateng Pajimatan activity, the facilities and services provided by the studio fulfill psycho-biological needs, in gathering activities, discussing marriage material using Javanese customs, and trying to provide livelihoods fulfill biological needs, the educational process carried out includes learning sesuluh (material), Gladhen Tumindak (practical activities), Nyekar dhateng Pajimatan activities and Nyinau Wewangunan Surakarta Palace activities, and rules in terms of dress meet instrumental needs, and learning Javanese culture with reference to Surakarta Palace meets integrative needs.